2023
DOI: 10.1007/s12664-022-01308-6
|View full text |Cite
|
Sign up to set email alerts
|

Utility of high-flow nasal oxygen in comparison to conventional oxygen therapy during upper gastrointestinal endoscopic procedures under sedation: A systematic review and meta-analyses

Abstract: Background Sedation and analgesia are the integral components of modern-day upper gastrointestinal (GI) endoscopic procedures. Irrespective of the sedative agent, hypoxia is the most commonly encountered unwarranted event with sedation. The current study intends to scrutinize whether high-flow nasal oxygen (HFNO) is advantageous for providing respiratory support during upper GI endoscopic procedures over other conventional low-flow oxygen delivery modalities, e.g. nasal cannula, facemask, etc. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
5
0
1
Order By: Relevance
“…However, these data are not consistent. Khanna et al [ 45 ], in a recent meta-analysis comparing HFNC vs. COT during the upper gastrointestinal endoscopic procedure under sedation, state that the evidence for improved oxygenation and decreased incidence of endoscopic procedure interruption is of low quality due to a lack of significant direct correspondence in terms of differences in population and HFNC schedules. In the same vein, Lee et al [ 46 ] in a meta-analysis do not demonstrate that HFNC reduces the overall incidence of hypoxaemia, explaining the discrepancies in the results between the different studies by the different statistical models used by each systematic review.…”
Section: Hfnc In Upper Gastrointestinal Endoscopymentioning
confidence: 99%
“…However, these data are not consistent. Khanna et al [ 45 ], in a recent meta-analysis comparing HFNC vs. COT during the upper gastrointestinal endoscopic procedure under sedation, state that the evidence for improved oxygenation and decreased incidence of endoscopic procedure interruption is of low quality due to a lack of significant direct correspondence in terms of differences in population and HFNC schedules. In the same vein, Lee et al [ 46 ] in a meta-analysis do not demonstrate that HFNC reduces the overall incidence of hypoxaemia, explaining the discrepancies in the results between the different studies by the different statistical models used by each systematic review.…”
Section: Hfnc In Upper Gastrointestinal Endoscopymentioning
confidence: 99%
“…To further strengthen the evidence and offer a comprehensive perspective, a very recent systematic review and meta-analysis by Khanna et al (2023) examined the benefits of HFOT as opposed to COT during upper gastrointestinal endoscopies with sedation. The study included data from eight controlled studies and one longitudinal study, encompassing a total of 3294 patients.…”
Section: The Role Of Hfot During Sedated Gi Endoscopymentioning
confidence: 99%
“…The aim was to assess the impact of HFOT on the duration of the procedures, interruption rates, occurrences of hypoxia, lowest SpO 2 levels, complications, total propofol dosage, and the satisfaction levels of both patients and endoscopists. While the findings suggested that the HFOT group experienced improved oxygenation, fewer procedural interruptions, and higher nadir SpO 2 levels, it is worth noting that the quality of the evidence was questioned because there was great variation between the studies regarding population and setting [78].…”
Section: The Role Of Hfot During Sedated Gi Endoscopymentioning
confidence: 99%
“…Apesar da segurança proporcionada pela intubação traqueal e anestesia geral, estas, muitas vezes demandam mais tempo para o despertar do paciente. Isso, aliado ao curto tempo operatório e às novas drogas disponíveis no mercado, com melhores perfis de segurança, sugerem que a sedação seja uma modalidade mais vantajosa que a anestesia geral nesses procedimentos (KHANNA et al, 2023).…”
Section: Introductionunclassified